2016
DOI: 10.3390/ijms17091506
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Immunotherapies for Multiple Myeloma

Abstract: Multiple myeloma (MM) is a disorder of terminally differentiated plasma cells characterized by clonal expansion in the bone marrow (BM). It is the second-most common hematologic malignancy. Despite significant advances in therapeutic strategies, MM remains a predominantly incurable disease emphasizing the need for the development of new treatment regimens. Immunotherapy is a promising treatment modality to circumvent challenges in the management of MM. Many novel immunotherapy strategies, such as adoptive cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 216 publications
0
22
0
Order By: Relevance
“…antigens such as SLAMF7, CD38, CD74, or CD138 39 , providing naturally processed HLA-presented ligands derived from intracellular domains of established membrane-bound tumor-associated antigens. Such HLA ligands represent promising targets for (i) low side effect single agent vaccine approaches in elderly patients or early disease states 21,28,40 , (ii) TCR-engineered T cells 41 , (iii) antibody-based approaches 42 , or (iv) novel approaches combining HLA-dependent and -independent antigens and treatments 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…antigens such as SLAMF7, CD38, CD74, or CD138 39 , providing naturally processed HLA-presented ligands derived from intracellular domains of established membrane-bound tumor-associated antigens. Such HLA ligands represent promising targets for (i) low side effect single agent vaccine approaches in elderly patients or early disease states 21,28,40 , (ii) TCR-engineered T cells 41 , (iii) antibody-based approaches 42 , or (iv) novel approaches combining HLA-dependent and -independent antigens and treatments 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Besides the selection of optimal target antigens for the development of clinically effective T-cell-based immunotherapies in MM, one must consider the profound immune defects that prevail in these patients and might impair the efficacy of inducing antigen-specific T-cell responses in vivo 22,47 . A major immunosuppressive mechanism in MM is the upregulation of inhibitory immune checkpoint molecules on T cells 22,39 . By employing PD-1/CTLA-4 blockade, we were able to overcome this mechanism and to induce multifunctional cytotoxic P(BCMA) B*18 -specific T cells, even in MM-derived samples.…”
Section: Discussionmentioning
confidence: 99%
“…To date treatment of MM has focused on stem cell transplantation, targeted agents such as the proteosome inhibitor bortezomib, immune modulation with lenalidomide, and standard and high dose cytotoxic chemotherapies. While many patients benefit from these therapies, relapse is common and new therapies are needed [74,75]. Recent areas of interest include immunotherapies that trigger the host anti-tumor immune response and thus far, the results are promising [75,76].…”
Section: Tam Receptors In Hematopoietic Malignanciesmentioning
confidence: 99%
“…While many patients benefit from these therapies, relapse is common and new therapies are needed [74,75]. Recent areas of interest include immunotherapies that trigger the host anti-tumor immune response and thus far, the results are promising [75,76]. Therapeutic approaches include checkpoint inhibitors, MM vaccines, adoptive T Cell Transfer [77], and monoclonal antibodies.…”
Section: Tam Receptors In Hematopoietic Malignanciesmentioning
confidence: 99%
“…75,76 Used as a single agent, daratumumab had a 36% response rate in patients with refractory myeloma. 77 Drent et al have demonstrated in preclinical work that anti-CD38 CAR-Ts proliferate, produce cytokines, and lyse CD38 1 MM cells; however, these CAR-Ts lysed not only CD38…”
Section: Cd38mentioning
confidence: 99%